FAITH AS DIALECTICAL INTERPLAY OF AFFECTION AND COGNITION IN NEWMAN AND “PANDAMA” (INTEGRATIVE SENSING) OF FILIPINO CHRISTIANS - Cacho, Rebecca (Asian Horizons, 2013)
No theology may claim to “fall from heaven” so to speak. All theological reflections are rooted in a specific time, culture and history of people. They are not raw realities but are always interpreted experiences. Theologies that fail to have recognizable reference to people’s contexts are futile because they would never touch their hearts. Newman recognized this when he said: “I say plainly I do not want to be converted by a smart syllogism; if I am asked to convert others by it. I say plainly I do not care to overcome their reason without touching their hearts.”